Contemporary stroke care delivered in a specialised stroke bay, a neurology ward and a medical ward in Greece - Theofanidis, Dimitrios; Fountouki, Antigoni; Savopoulos, Christos; Hatzitolios, Apostolos; Fitsioris, Xenofon; Rudolf, Jiobst (Health & Research Journal, 2019)
Introduction: Currently in Greece there are only two ‘stroke bays’ (SBs) and their efficacy compared to standard ward treatment has not been evaluated. Aim: To provide baseline data on stroke case-mix and compare death rates in two Greek hospitals (A+B, i.e. with & without a SB). Material and Methods: One hundrend sixty four acute stroke patients from two hospitals were consecutively selected in order to explore approaches to stroke care in three different types of care delivery settings. A descriptive design with group comparisons was employedand data gathering included patient case mix, age and length of stay (LOS), neurological status and death rates. Kaplan-Meier curves we reused for survival analysis and independent samples t test and Z test for group comparisons at p<0.05. Results: Of the 164 patients, 88 (44.4%, female) werein hospital A and 76 (42.1%, female) in hospital B. The mean age was 65.7 and 69.1 years respectively, LOS was 7.6 (3-18) and 7.3 days (1-26), while death rate was 6.8% and 10.5% respectively. Discussion: Survival analysis for the two hospitalsshowed that there are no statistically significant differences regarding death and survival rates between the two hospitals, even when one had a SB. Yet, the SB shows a statistically significant reduction in overall LOS. Conclusions: In societies where stroke units are not yet established, a SB might be an economical way of making use of (limited) available resources and raising nursing and medical standards of care by motivating the full potential of staff involved.